Artificial Macropores with Sandy Fillings Enhance Desalinization and Increase Plant Biomass in Two Contrasting Salt-Affected Soils - Yifu Zhang; Ruihong Zhang; Baofeng Zhang; Xiaobo Xi (Applied Sciences, 2021)
Salt accumulation in topsoil is a widespread restricting factor that limits agricultural production and threatens food security in arid and semi-arid regions. However, whether this upward enrichment was suppressed by macropores was less documented. Therefore, artificial macropores with sandy fillings (AMSF) method was proposed in this study. Soil column experiments showed a significant improvement of saturated hydraulic conductivity (Ks) by more than 260% under artificial macropore treatment. Freshwater irrigation was conducted to monitor the short-term water and salt movement. This research aimed at evaluating the potential benefit of AMSF method on soil desalinization in coastal farmland of northern China. The results demonstrated that downward movement of soil water was stimulated in AMSF method, accordingly, washing more salt ions out of top rooting zone. Particularly, 10 cm or more macropore depth treatments of AMSF method enhanced total desalinization by 52.1% to 176.6% in 0–30 cm soil layer, in comparison to the control group without macropore. Subsequent observations for alfalfa showed higher biomass by 20.8% under 15 cm macropore depth. The results here provided an exploration demonstration to pursue these studies with the ultimate goal of optimizing application strategies for amendment in coastal salt-affected lands of northern China.